2020
DOI: 10.1371/journal.ppat.1008562
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution analysis of Merkel Cell Polyomavirus in Merkel Cell Carcinoma reveals distinct integration patterns and suggests NHEJ and MMBIR as underlying mechanisms

Abstract: Merkel Cell Polyomavirus (MCPyV) is the etiological agent of the majority of Merkel Cell Carcinomas (MCC). MCPyV positive MCCs harbor integrated, defective viral genomes that constitutively express viral oncogenes. Which molecular mechanisms promote viral integration, if distinct integration patterns exist, and if integration occurs preferentially at loci with specific chromatin states is unknown. We here combined short and long-read (nanopore) next-generation sequencing and present the first high-resolution a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 85 publications
(152 reference statements)
2
20
0
Order By: Relevance
“…MMEJ is a Ku-independent, Polθ-dependent, DNA DSB repair pathway [26,[62][63][64] that could be involved aberrant IN-independent HIV-1 integration [47][48][49] and adeno-associated virus, papillomavirus and MCV integration [7,13,28,29]. We showed that a majority of the virus-host junctions bear 2-10 nts of MHS between MmuPV1 and host DNA.…”
Section: Plos Pathogensmentioning
confidence: 86%
See 2 more Smart Citations
“…MMEJ is a Ku-independent, Polθ-dependent, DNA DSB repair pathway [26,[62][63][64] that could be involved aberrant IN-independent HIV-1 integration [47][48][49] and adeno-associated virus, papillomavirus and MCV integration [7,13,28,29]. We showed that a majority of the virus-host junctions bear 2-10 nts of MHS between MmuPV1 and host DNA.…”
Section: Plos Pathogensmentioning
confidence: 86%
“…Microhomology sequences (MHS) are present at aberrant HIV-1 integration sites that were not mediated by integrase (IN) [47][48][49][50] and at the integration sites of adeno-associated virus, papillomavirus and MCV [13,28,29]. We analyzed the virus-host junction sequences by both RNA-seq and targeted DNA-seq by comparing the sequences of the MmuPV1 genome and the mouse genome.…”
Section: Identification Of Microhomology Sequences At Mmupv1 Integration Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…Integration of MCPyV into the host genome is not part of the viral life cycle, as the virus does not contain integrase, and occurs through DNA repair mechanisms, such as nonhomologous end joining (NHEJ) and microhomology-mediated end joining (MMEJ) [216].…”
Section: Merkel Cell Polyomavirus (Mcv)mentioning
confidence: 99%
“…Point mutations in other regions of the genome and truncations of the MCPyV LT C-terminal domain, however, are common in viral MCCs (Liu et al, 2016a ). Expression of the viral oncoproteins is largely driven by the preserved MCPyV promoter rather than endogenous promoters, though there are conflicting reports as to whether MCPyV is more likely to integrate into specific regions of chromatin (Doolittle-Hall et al, 2015 ; Czech-Sioli et al, 2020 ). Sequencing of integration sites in multiple MCC tumors reveal that initial recombination of a linearized MCPyV genome with the host genome could lead to transient circularization and amplification of the viral genome and neighboring host DNA (Starrett et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%